Conductive silver paste and preparation method thereof

By using combination components such as multi-dimensional micro-nano conductive silver powder and surface conductive liquid metal nanoparticles in conductive silver paste, a three-dimensional mesh conductive path is constructed, which solves the failure problem of low-temperature cured conductive layer under high mechanical deformation, and improves the flexible sensor electrical stability and bending resistance.

CN119274846APending Publication Date: 2025-01-07XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411571382.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing low-temperature cured conductive silver paste is prone to failure under high mechanical deformation and long-term cycling strain, resulting in unstable electrical connections and difficult to meet the needs of high-stability flexible sensors.

Method used

Using a combination of multi-dimensional micro-nano conductive silver powder, surface conductive liquid metal nanoparticles, multi-system organic resin bonding phase, enclosed curing agent and additive additives, the high conductivity and self-healing properties of liquid metals are used through multi-dimensional interface contact and the high conductivity and self-healing properties of liquid metals. , construct a three-dimensional network conductive path and optimize the curing process of silver paste to improve adhesion and bending resistance.

Benefits of technology

It significantly improves the bending resistance, adhesion and fatigue resistance of the conductive silver paste, improves the electrical stability of the conductive lines, and meets the continuous production needs of high stability and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119274846A_ABST
    Figure CN119274846A_ABST
Patent Text Reader

Abstract

The invention relates to conductive silver paste and a preparation method thereof, and relates to the technical field of low-temperature curing type conductive paste, the conductive silver paste comprises the following components: multi-dimensional micro-nano conductive silver powder, surface conductive type liquid metal nanoparticles, a multi-system organic resin binding phase, a closed curing agent, a mixed organic solvent and various additives; wherein the mass part of each component is as follows: the mass part of the multi-dimensional micro-nano conductive silver powder is 60-90; the mass part of the surface conductive liquid metal nanoparticles is 5-10; the mass part of the multi-system organic resin binding phase is 0.1-10; the mass part of the closed curing agent is 0.1-5 parts; the mass part of the mixed organic solvent is 5-20; the mass part of each additive is 0.1-10 parts. The bending resistance, the adhesive force and the fatigue resistance of the conductive silver paste are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present disclosure relate to the technical field of low-temperature curing conductive paste, and in particular to a method for electro-deposition of a metal grid line and a metal grid line. Background Art

[0002] The main components of conductive silver paste used in flexible printing scenarios may include conductive silver powder, organic carriers (such as organic polymer adhesive phase and organic solvent) and organic additives; therefore, the conductivity of the functional filler, the adaptability of the adhesive phase, the bonding strength of the organic carrier, the volatilization rate of the organic solvent and the curing process of the paste will affect the electrical and mechanical properties of the final paste.

[0003] At present, low-temperature curing silver paste products can basically meet the needs of conventional electronic products; however, the technical barriers for high-quality conductive silver paste for high-stability flexible sensors have not yet been broken through; among them, this technical barrier is mainly reflected in the failure of the low-temperature curing conductive layer caused by high mechanical deformation and long-term cyclic strain, and the unstable electrical connection caused by interface mismatch problems.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] The purpose of the present disclosure is to provide a method for electrodeposition of a metal grid line and a metal grid line, thereby overcoming the problems of poor adhesion and high bending resistance caused by the limitations and defects of the related art at least to a certain extent.

[0006] According to one aspect of the present disclosure, a conductive silver paste is provided, which comprises the following components: multi-dimensional micro-nano conductive silver powder, surface conductive liquid metal nanoparticles, multi-system organic resin binder phase, enclosed curing agent, mixed organic solvent and various additives; wherein the mass parts of each component are:

[0007] The mass proportion of the multi-dimensional micro-nano conductive silver powder is 60-90 parts;

[0008] The mass parts of the surface conductive liquid metal nanoparticles are 5-10 parts;

[0009] The mass proportion of the multi-system organic resin bonding phase is 0.1-10 parts;

[0010] The mass fraction of the blocked curing agent is 0.1-5 parts;

[0011] The mass parts of the mixed organic solvent are 5-20 parts;

[0012] The mass parts of each type of additive are 0.1-10 parts.

[0013] In an exemplary embodiment of the present disclosure, the multi-dimensional micro-nano conductive silver powder includes silver powders of various dimensions, shapes and particle sizes;

[0014] The plurality of silver powders of different dimensions, different shapes and different particle sizes include a plurality of silver nanowires, flaky silver powders and spherical silver powders;

[0015] The length of the silver nanowire is 20-60 μm, and the diameter of the silver nanowire is 10-30 nm;

[0016] The particle size of the flaky silver powder is 2.0-7.0 μm; the particle size of the spherical silver powder is 5-300 nm;

[0017] In the multi-dimensional micro-nano conductive silver powder, the silver nanowires account for 2%-15%, and the spherical silver powder accounts for 2%-30%.

[0018] In an exemplary embodiment of the present disclosure, the surface conductive liquid metal nanoparticles include metal gallium and a gallium alloy associated with the metal gallium;

[0019] The gallium alloy comprises at least one of a gallium-tin alloy, a gallium-indium alloy, a gallium-indium-tin alloy and a gallium-indium-tin-zinc alloy;

[0020] The surface conductive liquid metal nanoparticles are prepared by: (1) using gallium-based liquid metal composed of metal gallium and a gallium alloy associated with the metal gallium as an initial raw material, and adding a precursor solution to the initial raw material; (2) placing the initial raw material after adding the precursor solution into a microfluidic ultrasonic reaction device for reaction to obtain the surface conductive liquid metal nanoparticles;

[0021] The precursor solution includes multiple types of toluene, polyethylene vinyl acetate and diamino peroxide.

[0022] In an exemplary embodiment of the present disclosure, the multi-system organic resin binder phase is a mixture of polyester resin, acrylic resin and polyurethane;

[0023] The polyester resin is a polyester resin with a linear structure and a hydroxyl terminal, and the proportion of the polyester resin in the multi-system organic resin binder phase is 35%-65%.

[0024] In an exemplary embodiment of the present disclosure, the blocked curing agent includes aliphatic diisocyanate, and the deblocking temperature of the blocked curing agent is 100-150°C.

[0025] In an exemplary embodiment of the present disclosure, the mixed organic solvent includes two or more of butyl carbitol, terpineol, N-methyl pyrrolidone, alkylbenzene, butyl carbitol acetate and mixed dibasic esters.

[0026] In an exemplary embodiment of the present disclosure, the various additives include modified urea, polysiloxane, organic bentonite and polyamide wax; wherein, among the various additives, the modified urea accounts for 0.2%-1%, the polysiloxane accounts for 0.1%-4%, the organic bentonite accounts for 0.1%-1%, and the polyamide wax accounts for 0.1%-3%.

[0027] According to one aspect of the present disclosure, there is provided a method for preparing a conductive silver paste according to any one of the above items, comprising:

[0028] (1) Weighing ferric chloride, silver nitrate, ethylene glycol and polyvinyl pyrrolidone surfactant by weight, adding ferric chloride, silver nitrate, ethylene glycol and polyvinyl pyrrolidone surfactant into a three-necked round-bottom flask, and heating at 140° C. for 4 h to prepare a dispersion of silver nanowires;

[0029] (2) weighing toluene, polyethylene vinyl acetate, diamino peroxide and liquid metal by weight, adding the toluene, polyethylene vinyl acetate, diamino peroxide and liquid metal into an ultrasonic reaction microfluidic channel, ultrasonicating at 30° C. for 20 min to prepare a dispersion of the surface conductive liquid metal nanoparticles, and centrifuging the dispersion of the surface conductive liquid metal nanoparticles to obtain ultrafine surface conductive liquid metal nanoparticles;

[0030] (3) taking a plurality of organic resin binder phases and a plurality of organic solvents by weight, and adding the organic resin binder phases and the organic solvents to the prepared silver nanowire dispersion to obtain an organic mixed solution containing silver nanowires;

[0031] (4) placing the organic mixed solution containing the silver nanowires into a high-speed dispersion kettle, and stirring the organic mixed solution containing the silver nanowires at a constant temperature until it is homogeneous, thereby obtaining an organic carrier containing the silver nanowires;

[0032] (5) adding flaky silver powder and spherical silver powder to an organic carrier containing silver nanowires to obtain an organic mixed solution containing silver nanowires and nano-silver powder, and placing the organic mixed solution containing silver nanowires and nano-silver powder into a planetary mixer and continuing to stir to prepare a uniform slurry;

[0033] (6) adding an organic additive and a blocked curing agent to the slurry in the uniform state, continuing stirring to adjust the viscosity and thixotropic properties of the slurry in the uniform state, and placing the slurry after the viscosity and performance are adjusted into a three-roll grinder to adjust the slurry fineness to obtain the final self-repairing low-temperature curing conductive silver paste.

[0034] In an exemplary embodiment of the present disclosure, in the process of preparing the dispersion of silver nanowires, the preparation method used is a polyol method;

[0035] In the process of preparing a dispersion of silver nanowires based on the polyol method, after the isothermal reaction in a three-necked round-bottom flask, the three-necked round-bottom flask needs to be quickly placed in ice cubes for cooling, and acetone is added to the cooled three-necked round-bottom flask and centrifuged several times to obtain the dispersion of the silver nanowires.

[0036] In an exemplary embodiment of the present disclosure, the rotation speed of the high-speed dispersing kettle is 1000-5000 rpm, the dispersing temperature of the high-speed dispersing kettle is controlled at 65-95° C., and the stirring and mixing time is 10-30 minutes;

[0037] The revolution speed of the planetary mixer is 1000-2200 rpm, and the rotation speed of the planetary mixer is 700-1400 rpm;

[0038] The spacing of the three-roll mill is adjusted to 2-25 μm, and the rotation speed is controlled at 300-500 rpm;

[0039] In the process of curing the uniform slurry, the curing temperature used is 100-150° C., and the curing time used is 10-30 minutes.

[0040] A conductive silver paste provided in an exemplary embodiment of the present disclosure, on the one hand, because multidimensional micro-nano conductive silver powder, surface conductive liquid metal nanoparticles, multi-system organic resin bonding phase, closed curing agent, mixed organic solvent and various additives are added to the conductive silver paste, compared with other conductive silver pastes in the relevant technical solutions, the addition of multidimensional micro-nano conductive silver powder, surface conductive liquid metal nanoparticles and closed curing agent improves the bending resistance, adhesion and fatigue resistance of the conductive silver paste; on the other hand, the conductive silver paste can also effectively improve the dispersion stability of the multidimensional micro-nano composite silver powder, optimize the curing process of the silver paste, improve the adhesion and bending resistance of the silver paste after curing, and greatly improve the electrical stability of the conductive circuit.

[0041] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0043] Figure 1 The flowchart schematically shows a method for preparing a conductive silver paste according to an exemplary embodiment of the present disclosure.

[0044] Figure 2 A scanning electron microscope image of a silver nanowire obtained according to an example embodiment of the present disclosure is schematically shown.

[0045] Figure 3 A diagram schematically shows a microfluidic ultrasonic reaction device required for preparing a conductive silver paste according to an exemplary embodiment of the present disclosure.

[0046] Figure 4 A scanning electron microscope image of surface conductive liquid metal nanoparticles obtained according to an exemplary embodiment of the present disclosure is schematically shown. DETAILED DESCRIPTION

[0047] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0048] The terms "a", "an", "the" and "said" used in this specification are used to indicate the presence of one or more elements / components, etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that there may be additional elements / components, etc. in addition to the listed elements / components, etc.; the terms "first" and "second" etc. are used only as labels and are not intended to limit the quantity of their objects.

[0049] With the rapid development of the electronics industry, in the face of increasingly complex and changeable monitoring environments, sensors need to meet the characteristics of high flexibility, high ductility, high bending and shape adaptability while achieving high integration of sensing technology and miniaturization of components. Therefore, sensors based on flexible substrates have broad application prospects in the fields of wearable devices, biomedical electronics, smart packaging and space environment monitoring in recent years, and flexible printing of functional electronic pastes is the key to realizing flexible sensors. At present, most flexible substrates, such as polyimide films, polyethylene terephthalate films, elastic materials and hydrogels, have poor high temperature resistance. Therefore, the conductive silver paste for flexible printing is required to have low curing temperature and fast curing characteristics to avoid causing the failure of the flexible substrate; at the same time, the low-temperature curing silver layer needs to meet the requirements of high stability and low-cost continuous production on the basis of low square resistance, high hardness, high adhesion, high resolution and high bending resistance.

[0050] In the relevant technical solutions, the main components of the conductive silver paste for flexible printing are conductive silver powder, organic carrier (organic polymer adhesive phase and organic solvent) and organic additives. Therefore, the conductivity of the functional filler, the adaptability of the adhesive phase, the bonding strength of the organic carrier, the volatilization rate of the solvent and the curing process of the paste will affect the electrical and mechanical properties of the final paste. At present, the products of low-temperature curing silver paste in the relevant technical solutions basically meet the needs of conventional electronic products, but the technical barriers for high-stability flexible sensors with high-quality conductive silver paste have not yet been broken through, mainly manifested in the failure of the low-temperature curing conductive layer caused by high mechanical deformation and long-term cyclic strain and the unstable electrical connection caused by interface mismatch problems. Therefore, it is urgent to develop a conductive silver paste for flexible sensors with excellent adhesion and high bending resistance to ensure the stability of the sensor during service.

[0051] Based on this, the exemplary embodiment of the present disclosure first provides a conductive silver paste, which may include the following components: multi-dimensional micro-nano conductive silver powder, surface conductive liquid metal nanoparticles, a multi-system organic resin bonding phase, a closed curing agent, a mixed organic solvent and various additives; wherein the mass parts of each component are: the mass part of the multi-dimensional micro-nano conductive silver powder is 60-90 parts; the mass part of the surface conductive liquid metal nanoparticles is 5-10 parts; the mass part of the multi-system organic resin bonding phase is 0.1-10 parts; the mass part of the closed curing agent is 0.1-5 parts; the mass part of the mixed organic solvent is 5-20 parts; the mass part of various additives is 0.1-10 parts.

[0052] The conductive silver paste provided in the exemplary embodiments of the present disclosure, on the one hand, because multi-dimensional micro-nano conductive silver powder, surface conductive liquid metal nanoparticles, multi-system organic resin bonding phase, closed curing agent, mixed organic solvent and various additives are added to the conductive silver paste, compared with other conductive silver pastes in the relevant technical solutions, the addition of multi-dimensional micro-nano conductive silver powder, surface conductive liquid metal nanoparticles and closed curing agent improves the bending resistance, adhesion and fatigue resistance of the conductive silver paste; on the other hand, the conductive silver paste can also effectively improve the dispersion stability of the multi-dimensional micro-nano composite silver powder, optimize the curing process of the silver paste, improve the adhesion and bending resistance of the silver paste after curing, and greatly improve the electrical stability of the conductive circuit.

[0053] Hereinafter, each component included in the above-mentioned conductive silver paste will be explained and illustrated in detail.

[0054] (1) Multidimensional micro-nano conductive silver powder. Specifically, the multidimensional micro-nano conductive silver powder described in the exemplary embodiments of the present disclosure may include silver powders of various dimensions, shapes and particle sizes; wherein the silver powders of various dimensions, shapes and particle sizes may include, but are not limited to, various types of silver nanowires, flaky silver powders and spherical silver powders; that is, the different dimensions are reflected in that the multidimensional micro-nano conductive silver powder includes not only silver nanowires but also silver powders, the different shapes are reflected in that the multidimensional micro-nano conductive silver powder includes linear silver powders, flaky silver powders and spherical silver powders; the different particle sizes are reflected in that the lengths and diameters of the silver nanowires, flaky silver powders and spherical silver powders included in the multidimensional micro-nano conductive silver powders are different. Specifically, in actual application, the length of the silver nanowire is 20-60μm, and the diameter of the silver nanowire is 10-30nm; further, the particle size of the flaky silver powder is 2.0-7.0μm; the particle size of the spherical silver powder is 5-300nm; at the same time, in the multi-dimensional micro-nano conductive silver powder, the proportion of silver nanowires is 2%-15%, and the proportion of spherical silver powder is 2%-30%.

[0055] (2) Surface conductive liquid metal nanoparticles. Specifically, the composition of the surface conductive liquid metal nanoparticles described in the exemplary embodiments of the present disclosure is metallic gallium and gallium alloys associated with metallic gallium; the gallium alloys described herein may include but are not limited to pure gallium, gallium-tin alloys, gallium-indium alloys, gallium-indium-tin alloys, and gallium-indium-tin-zinc alloys, etc.; at the same time, the surface conductive liquid metal nanoparticles described herein are prepared by the following method: (1) Gallium-based liquid metal composed of metallic gallium and gallium alloys associated with metallic gallium is used as the initial raw material, and a precursor solution is added to the initial raw material; (2) the initial raw material after the precursor solution is added is placed in a microfluidic ultrasonic reaction device for reaction to obtain surface conductive liquid metal nanoparticles; wherein the precursor solution includes toluene, polyethylene vinyl acetate, diamino peroxide, etc.

[0056] (3) Multi-system organic resin binder phase. Specifically, the multi-system organic resin binder phase described in the exemplary embodiments of the present disclosure is a mixture of polyester resin, acrylic resin and polyurethane; wherein the polyester resin is a linear polyester resin with hydroxyl terminal, and the proportion of the polyester resin in the multi-system organic resin binder phase is 35%-65%.

[0057] (4) Blocked curing agent: Specifically, the blocked curing agent described in the exemplary embodiment of the present disclosure includes aliphatic diisocyanate, and the deblocking temperature of the blocked curing agent is 100-150°C.

[0058] (5) Mixed organic solvents. Specifically, the mixed organic solvents described in the exemplary embodiments of the present disclosure include two or more of butyl carbitol, terpineol, N-methyl pyrrolidone, alkylbenzene, butyl carbitol acetate, and mixed dibasic esters.

[0059] (6) Various additives. Specifically, the various additives described in the exemplary embodiments of the present disclosure include various types of modified urea, polysiloxane, organic bentonite, and polyamide wax; among the various additives, the proportion of modified urea is 0.2%-1%, the proportion of polysiloxane is 0.1%-4%, the proportion of organic bentonite is 0.1%-1%, and the proportion of polyamide wax is 0.1%-3%.

[0060] So far, the conductive silver paste described in the exemplary embodiments of the present disclosure has been fully realized. Based on the above-mentioned contents, it can be known that the conductive silver paste described in the exemplary embodiments of the present disclosure, through the multi-dimensional conductive material interface contact, takes advantage of the high conductivity and self-healing property of liquid metal to construct a self-repairing three-dimensional mesh conductive path in the paste, thereby improving the electrical connection stability during the flexible deformation of the sensor; by means of the hydrogen bonding between the hydroxyl groups on the multi-system organic resin bonding phase molecules and the silver powder, the dispersion stability of the conductive phase is improved, so that the conductive silver paste not only has excellent adhesion and low square resistance characteristics, but also has high stability and anti-bending properties on a flexible substrate. Furthermore, the conductive silver paste described in the exemplary embodiments of the present disclosure can not only improve the bending resistance, adhesion and fatigue resistance of the low-temperature curing conductive silver paste to overcome the technical defects of the silver paste at this stage; it can also provide a low-temperature curing conductive silver paste that meets the technical indicators such as low square resistance, high hardness, high adhesion, high resolution and high bending resistance. The conductive silver paste can effectively improve the dispersion stability of micro-nano composite silver powder, optimize the curing process of the silver paste, improve the adhesion and bending resistance of the silver paste after curing, and greatly improve the electrical stability of the conductive circuit.

[0061] The exemplary embodiment of the present disclosure also provides a method for preparing a conductive silver paste. Figure 1As shown, the preparation method of the conductive silver paste comprises the following steps:

[0062] Step S110, weighing ferric chloride, silver nitrate, ethylene glycol and polyvinyl pyrrolidone surfactant by weight, adding ferric chloride, silver nitrate, ethylene glycol and polyvinyl pyrrolidone surfactant into a three-necked round-bottom flask, and heating the reaction at 140° C. for 4 hours to prepare a dispersion of silver nanowires;

[0063] Step S120, weighing toluene, polyethylene vinyl acetate, diamino peroxide and liquid metal by weight, and adding the toluene, polyethylene vinyl acetate, diamino peroxide and liquid metal into an ultrasonic reaction microfluidic channel, ultrasonicating at 30° C. for 20 min to prepare a dispersion of surface conductive liquid metal nanoparticles, and centrifuging the dispersion of surface conductive liquid metal nanoparticles to obtain ultrafine surface conductive liquid metal nanoparticles;

[0064] Step S130, taking a plurality of organic resin binder phases and a plurality of organic solvents by weight, and adding each organic resin binder phase and each organic solvent to the prepared silver nanowire dispersion to obtain an organic mixed solution containing silver nanowires;

[0065] Step S140, placing the organic mixed solution containing the silver nanowires into a high-speed dispersing kettle, and stirring the organic mixed solution containing the silver nanowires to a homogeneous state under a constant temperature state to obtain an organic carrier containing the silver nanowires;

[0066] Step S150, adding flaky silver powder and spherical silver powder to an organic carrier containing silver nanowires to obtain an organic mixed solution containing silver nanowires and nano-silver powder, and placing the organic mixed solution containing silver nanowires and nano-silver powder into a planetary mixer and continuing to stir to prepare a uniform slurry;

[0067] Step S160, adding an organic additive and a blocked curing agent to the uniform slurry, continuing stirring to adjust the viscosity and thixotropic properties of the uniform slurry, and placing the slurry after viscosity and performance adjustment into a three-roll grinder to adjust the slurry fineness to obtain the final self-repairing low-temperature curing conductive silver paste.

[0068] In an exemplary embodiment, in the process of preparing a dispersion of silver nanowires, the preparation method used is a polyol method; in the process of preparing a dispersion of silver nanowires based on the polyol method, after a constant temperature reaction in a three-necked round-bottom flask, the three-necked round-bottom flask needs to be quickly placed in ice cubes for cooling, and acetone is added to the cooled three-necked round-bottom flask and centrifuged several times to obtain a dispersion of silver nanowires.

[0069] In an exemplary embodiment, the rotation speed of the high-speed dispersion kettle is 1000-5000 rpm, the dispersion temperature of the high-speed dispersion kettle is controlled at 65-95°C, and the stirring and mixing time is 10-30 minutes; the revolution speed of the planetary mixer is 1000-2200 rpm, and the rotation speed of the planetary mixer is 700-1400 rpm; the spacing of the three-roll grinder is adjusted to 2-25 μm, and the rotation speed is controlled at 300-500 rpm; in the process of curing the uniform slurry, the curing temperature used is 100-150°C, and the curing time used is 10-30min.

[0070] The following will further explain and illustrate the specific preparation process of the conductive silver paste. Specifically, in the preparation process of the conductive silver paste, first, iron chloride, silver nitrate, ethylene glycol and polyvinyl pyrrolidone surfactant are weighed by weight and added to a three-necked round-bottom flask, and heated at 140°C to react to prepare a silver nanowire dispersion; wherein, the method for preparing the silver nanowire dispersion is a polyol method, which requires a constant temperature reaction at 140°C for 4 hours, and then the round-bottom flask is quickly placed in ice to cool, and acetone is added and centrifuged several times to finally obtain a silver nanowire dispersion; wherein, the electron microscope scanning image of the obtained silver nanowire can be referred to Figure 2 As shown; secondly, toluene, polyethylene vinyl acetate, diammonium peroxide and liquid metal are weighed by weight and added to the ultrasonic reaction microchannel, and the surface conductive liquid metal nanoparticle dispersion is prepared by ultrasonication at 30°C for 20 minutes, and ultrafine liquid metal nanoparticles are obtained by centrifugation; then, a variety of organic binder phase resins and organic solvents are added by weight to the prepared silver nanowire dispersion, and stirred at a constant temperature in a high-speed dispersion kettle until a homogeneous state is obtained; wherein the speed of the high-speed dispersion kettle is 1000-5000 rpm, the dispersion temperature is controlled at 65-95°C, and the stirring and mixing time is 10-30 minutes; further, liquid metal nanoparticles, lamellar silver powder and nano-spherical silver are added in small amounts and multiple times. The powder is added to an organic carrier containing silver nanowires, and is continuously stirred in a planetary mixer to prepare a uniform slurry; wherein, the revolution speed of the planetary mixer is 1000-2200 rpm, and the rotation speed is 700-1400 rpm; the spacing of the three-roll grinder is adjusted to 2-25 μm, and the rotation speed is controlled at 300-500 rpm; further, an appropriate amount of organic additives and a blocked curing agent are added, and stirring is continued to adjust the viscosity and thixotropic properties of the slurry; wherein, the curing process of the conductive silver paste is: temperature 100-150°C, time 10-30min; finally, the prepared slurry is subjected to a three-roll grinder to adjust the slurry fineness to obtain the final self-repairing low-temperature curing conductive silver paste.

[0071] At this point, the preparation method of the conductive silver paste described in the exemplary embodiment of the present disclosure has been fully realized. Compared with the related art, the preparation method of the conductive silver paste described in the exemplary embodiment of the present disclosure has the following advantages and beneficial effects: on the one hand, the conductive silver paste obtained by the preparation method of the conductive silver paste described in the exemplary embodiment of the present disclosure has excellent bending resistance; at the same time, the preparation method of the conductive silver paste described in the exemplary embodiment of the present disclosure breaks through the single formula design of the traditional low-temperature curing conductive silver paste, introduces surface conductive liquid metal nanoparticles, and takes advantage of its high conductivity, self-healing and fluidity, and from the perspective of multi-dimensional micro-nano conductive silver powder, multi-system bonding phase compounding and multi-level interface regulation, a new type of flexible sensor with high bending resistance and self-healing low-temperature curing conductive silver paste is prepared; on the other hand, through high aspect ratio silver nanowires, lamellar micron silver powder and spherical nano silver particles The multi-dimensional interface contact is used to construct a three-dimensional network conductive path in the slurry, thereby improving the conductive stability of the sensor during flexible deformation; with the help of the high conductivity and self-healing properties of liquid metal nanoparticles, the cracks that appear after the silver paste layer is bent are repaired, and the interface synergy is improved; on the other hand, the hydroxyl groups on the polyester resin and polyurethane resin molecules are used to hydrogen bond with the conductive functional phase silver powder and polymethyl methacrylate to improve the dispersion stability of the conductive phase; the composition and proportion of the composite bonding phase of blocked isocyanate, polyester resin, polyurethane and acrylic resin are regulated to ensure the low-temperature rapid curing of the slurry; finally, additives such as thixotropic agents, defoaming agents, coupling agents, etc. are introduced to improve the printing adaptability of the slurry, so that the final conductive silver paste has excellent high bending resistance, strong adhesion and high conductivity.

[0072] Hereinafter, the conductive silver paste and the method for preparing the conductive silver paste described in the exemplary embodiments of the present disclosure will be further explained and illustrated in conjunction with specific embodiments.

[0073] Embodiment 1: This embodiment provides a high bending resistance self-repairing low temperature curing conductive silver paste for flexible sensors and a preparation method thereof:

[0074] In this embodiment, the raw materials include the following components by weight: 60 parts of multi-dimensional micro-nano conductive silver powder, 5 parts of liquid metal nanoparticles, 12 parts of multi-system organic resin bonding phase, 3 parts of blocked curing agent, 15 parts of mixed organic solvent, and 5 parts of additives. Among them, the micro-nano conductive silver powder includes 35 parts of 7.5μm flaky metal silver powder, 20 parts of 50nm granular metal silver powder and 5 parts of self-made silver nanowires (length 50μm, diameter 30nm); the multi-system organic resin bonding phase includes 5 parts of hydroxyl-terminated polyester resin, 2 parts of acrylic resin, 2 parts of chloroacetic resin and 3 parts of polyurethane elastomer; the blocked curing agent is an aliphatic diisocyanate with a deblocking temperature of 130°C; the mixed organic solvent includes 3 parts of pine alcohol, 2 parts of butyl carbitol acetate and 10 parts of mixed dibasic esters; the organic additive includes 1.0 parts of modified urea, 0.7 parts of polysiloxane, 0.3 parts of organic bentonite and 3 parts of polyamide wax.

[0075] The specific preparation process is as follows: (1) Weigh ferric chloride, silver nitrate, ethylene glycol and polyvinyl pyrrolidone surfactant by weight and add them to a three-necked round-bottom flask, and heat at 140°C for 4 hours to prepare a silver nanowire dispersion. Specifically: take a certain amount of ethylene glycol solution and add it to a three-necked round-bottom flask, put the round-bottom flask into an oil bath, and heat it at 140°C; then add appropriate amounts of ferric chloride, silver nitrate, and polyvinyl pyrrolidone solids to 10mL of ethylene glycol solution respectively; then add the four solutions to the round-bottom flask in turn and mix evenly, and keep heating at 140°C for 4 hours. After the reaction is completed, take the round-bottom flask out of the oil bath and put it in ice to cool, and add the solution to a centrifuge tube containing acetone and centrifuge at high speed (2000rpm) to retain the silver nanowires in the lower layer until the final high-concentration silver nanowire dispersion is obtained; (2) Weigh toluene, polyethylene vinyl acetate, and diammonium peroxide by weight and add them to a flask such as Figure 3 The precursor solution of the microfluidic ultrasonic reaction system shown in the figure is added to the dropper; then, the gallium-tin alloy is weighed and added to the liquid metal dropper containing toluene; further, the process parameters such as the power, temperature and time of the ultrasonic system are adjusted to prepare a nano-scale surface conductive liquid metal nanoparticle dispersion. The collected dispersion is transferred to a centrifuge tube and centrifuged at high speed (3500rpm) for cleaning, and the precipitate is vacuum dried (80℃12h) to obtain the final nano-scale surface conductive liquid metal nanoparticles; the electron microscope scanning image of the obtained nano-scale surface conductive liquid metal nanoparticles can be referred to Figure 4As shown; (3) adding 5 parts of hydroxyl-terminated polyester resin, 2 parts of acrylic resin, 2 parts of chloroacetic acid resin, 3 parts of polyurethane elastomer and 15 parts of mixed organic solvent (the organic solvent includes 3 parts of pine alcohol, 2 parts of butyl carbitol acetate and 10 parts of mixed dibasic ester) by weight to the silver nanowire dispersion prepared in step (1), and mixing and stirring at 1000 rpm in a high-speed dispersion kettle at 75°C until homogeneous; (4) adding 5 parts of liquid metal nanoparticles, 35 parts of lamellar silver powder and 20 parts of nano-spherical silver powder to the constant temperature high-speed dispersion kettle of step (3) in small amounts and multiple times, stirring at high speed for 20 minutes, and then transferring to a planetary stirring degassing machine and continuing to stir for 5 minutes; (5) continuing to add the modified 0.5 parts of urea, 0.5 parts of polysiloxane, 1 part of organic bentonite and 3 parts of polyamide wax are added, and after degassing and stirring for 10 minutes, the mixed slurry is rolled on a three-roll grinder, and the roller spacing is adjusted to 25μm / 12μm; 12μm / 7μm; 7μm / 3μm, so that the slurry fineness is less than 5μm, to prepare the final conductive silver paste; (6) the silver paste prepared in step (5) is screen-printed on a polyethylene terephthalate film (screen printing area: 1×1cm) through a 350 mesh screen, and the printed sample is placed in a constant temperature drying oven at 130°C and dried for 20 minutes, and then taken out for performance tests, including fineness, viscosity, square resistance, hardness, adhesion and bending resistance tests.

[0076] Embodiment 2: This embodiment provides a high bending resistance self-repairing low temperature curing conductive silver paste for flexible sensors and a preparation method thereof:

[0077] In this embodiment, the raw materials include the following components by weight: 60 parts of multi-dimensional micro-nano conductive silver powder, 5 parts of liquid metal nanoparticles, 12 parts of multi-system organic resin bonding phase, 3 parts of blocked curing agent, 15 parts of mixed organic solvent, and 5 parts of additives. Among them, the micro-nano conductive silver powder includes 35 parts of 7.5μm flake metal silver powder, 15 parts of 50nm granular (i.e. spherical) metal silver powder and 10 parts of self-made silver nanowires (length 50μm, diameter 30nm); the multi-system organic resin bonding phase includes 5 parts of hydroxyl-terminated polyester resin, 2 parts of acrylic resin, 2 parts of chloroacetic resin and 3 parts of polyurethane elastomer; the blocked curing agent is 3 parts of aliphatic diisocyanate, and the deblocking temperature is 130°C; the mixed organic solvent includes 3 parts of pine alcohol, 2 parts of butyl carbitol acetate and 10 parts of mixed dibasic esters; the organic additive includes 1.0 parts of modified urea, 0.7 parts of polysiloxane, 0.3 parts of organic bentonite and 3 parts of polyamide wax.

[0078] The specific preparation process is as follows: (1) Weigh ferric chloride, silver nitrate, ethylene glycol and polyvinyl pyrrolidone surfactant by weight and add them to a three-necked round-bottom flask, and heat at 140°C for 4 hours to prepare a silver nanowire dispersion. Specifically: take a certain amount of ethylene glycol solution and add it to a three-necked round-bottom flask, put the round-bottom flask into an oil bath, and heat it at 140°C; then add appropriate amounts of ferric chloride, silver nitrate, and polyvinyl pyrrolidone solids to 10mL of ethylene glycol solution respectively; then add the four solutions to the round-bottom flask in turn and mix evenly, and keep heating at 140°C for 4 hours. After the reaction is completed, take the round-bottom flask out of the oil bath and put it in ice to cool, and add the solution to a centrifuge tube containing acetone and centrifuge at high speed (2000rpm) to retain the silver nanowires in the lower layer until the final high-concentration silver nanowire dispersion is obtained; (2) Weigh toluene, polyethylene vinyl acetate, and diammonium peroxide by weight and add them to a flask such as Figure 3 The precursor solution is added to the dropper of the microfluidic ultrasonic reaction system shown in the figure; then, the gallium-tin alloy is weighed and added to the liquid metal dropper containing toluene; further, the process parameters such as the power, temperature and time of the ultrasonic system are adjusted to prepare a nanoscale surface conductive liquid metal nanoparticle dispersion. The collected dispersion was transferred to a centrifuge tube and washed by high-speed centrifugation (3500 rpm), and the precipitate was vacuum dried (80°C for 12 h) to obtain the final nano-scale surface conductive liquid metal nanoparticles; (3) 5 parts of hydroxyl-terminated polyester resin, 2 parts of acrylic resin, 2 parts of chloroacetic acid resin, 3 parts of polyurethane elastomer and 15 parts of mixed organic solvent (the organic solvent includes 3 parts of pine alcohol, 2 parts of butyl carbitol acetate and 10 parts of mixed dibasic ester) were added to the silver nanowire dispersion prepared in step (1) by weight, and mixed and stirred at 1000 rpm in a high-speed dispersion kettle at 75°C until homogeneous; (4) 5 parts of liquid metal nanoparticles, 35 parts of lamellar silver powder and 15 parts of nano-spherical silver powder were added in small amounts and multiple times to the constant temperature high-speed dispersion kettle of step (3), and stirred at high speed. After stirring for 20 minutes, transfer to a planetary stirring degassing machine and continue stirring for 5 minutes; (5) continue to add 1 part of modified urea, 0.7 parts of polysiloxane, 0.3 parts of organic bentonite and 3 parts of polyamide wax, degas and stir for 10 minutes, and then roll the mixed slurry through a three-roll grinder, and adjust the roller spacing to 25μm / 12μm; 12μm / 7μm; 7μm / 3μm, so that the slurry fineness is less than 5μm, and the final conductive silver paste is prepared; (6) the silver paste prepared in step (5) is screen-printed on a polyethylene terephthalate film (screen printing area: 1×1cm) through a 350 mesh screen, and the printed sample is placed in a constant temperature drying oven at 130°C and dried for 20 minutes, and then taken out for performance testing, including fineness, viscosity, square resistance, hardness, adhesion and bending resistance tests.

[0079] Comparative Example 1: This embodiment provides a high bending resistance self-repairing low temperature curing conductive silver paste for a flexible sensor and a preparation method thereof:

[0080] In this embodiment, the raw materials include the following components by weight: 60 parts of multi-dimensional micro-nano conductive silver powder, 12 parts of multi-system organic resin bonding phase, 3 parts of blocked curing agent, 15 parts of mixed organic solvent, and 5 parts of additives. Among them, the micro-nano conductive silver powder includes 65 parts of 7.5μm flake metal silver powder; the multi-system organic resin bonding phase includes 12 parts of hydroxyl terminal polyester resin; the blocked curing agent is 3 parts of aliphatic diisocyanate, and the deblocking temperature is 130°C; the mixed organic solvent includes 15 parts of mixed dibasic ester; the organic additive includes 1.0 part of modified urea, 0.7 part of polysiloxane, 0.3 part of organic bentonite and 3 parts of polyamide wax.

[0081] The specific preparation process is as follows: (1) Weigh ferric chloride, silver nitrate, ethylene glycol and polyvinyl pyrrolidone surfactant by weight and add them to a three-necked round-bottom flask, and heat at 140°C for 4 hours to prepare a silver nanowire dispersion. Specifically: take a certain amount of ethylene glycol solution and add it to a three-necked round-bottom flask, put the round-bottom flask into an oil bath, and heat it at 140°C; then add appropriate amounts of ferric chloride, silver nitrate, and polyvinyl pyrrolidone solids to 10mL of ethylene glycol solution respectively; then add the four solutions to the round-bottom flask in turn and mix evenly, and keep heating at 140°C for 4 hours. After the reaction is completed, take the round-bottom flask out of the oil bath and put it in ice to cool, and add the solution to a centrifuge tube containing acetone and centrifuge at high speed (2000rpm) to retain the silver nanowires in the lower layer until the final high-concentration silver nanowire dispersion is obtained; (2) Weigh toluene, polyethylene vinyl acetate, and diammonium peroxide by weight and add them to a flask such as Figure 3The precursor solution of the microfluidic ultrasonic reaction system shown in the figure is added to the dropper; then, the gallium-tin alloy is weighed and added to the liquid metal dropper containing toluene; further, the process parameters such as the power, temperature and time of the ultrasonic system are adjusted to prepare a nano-scale surface conductive liquid metal nanoparticle dispersion. The collected dispersion is transferred to a centrifuge tube and washed by high-speed centrifugation (3500rpm), and the precipitate is vacuum dried (80℃12h) to obtain the final nano-scale surface conductive liquid metal nanoparticles; (3) 12 parts of hydroxyl-terminated polyester resin and 15 parts of mixed organic solvent (the organic solvent includes 15 parts of mixed dibasic ester) are added to the silver nanowire dispersion prepared in step (1) by weight, and mixed and stirred at 1000 rpm in a high-speed dispersion kettle at 75℃ until homogeneous; (4) 65 parts of flaky silver powder are added to the constant temperature high-speed dispersion kettle of step (3) in small amounts and multiple times, and after high-speed stirring for 20 minutes, it is transferred to a planetary stirring degassing machine and continued to stir for 5 minutes; (5) 1 part of modified urea, 0.7 part of polysiloxane, 0.3 part of organic bentonite and 3 parts of polyamide wax were added successively, and after degassing and stirring for 10 minutes, the mixed slurry was rolled on a three-roll mill, and the roller spacing was adjusted to 25 μm / 12 μm, 12 μm / 7 μm and 7 μm / 3 μm, respectively, so that the slurry fineness was less than 5 μm, and the final conductive silver paste was prepared; (6) the silver paste prepared in step (5) was screen-printed on a polyethylene terephthalate film (screen printing area: 1×1 cm) through a 350 mesh screen, and the printed sample was placed in a constant temperature drying oven at 130° C. and dried for 20 minutes, and then taken out for performance tests, including fineness, viscosity, square resistance, hardness, adhesion and bending resistance tests.

[0082] Further, to avoid being too cumbersome, Examples 3-5 and Comparative Examples 2-3 are omitted here; and the specific implementations of Examples 3-5 and Comparative Examples 2-3 are similar to those of Examples 1-2 and Comparative Example 1, except that the components or weight portions of the components used are different. At the same time, the specific components and weight portions of Examples 3-5 and Comparative Examples 2-3 are shown in Table 1 below.

[0083] Table 1 Specific components and weight parts of Examples 3-5 and Comparative Examples 2-3

[0084]

[0085] Further, the performance test results of the conductive silver paste obtained based on Examples 1-5 and the conductive silver paste obtained based on Comparative Examples 1-3 can be specifically referred to as shown in Table 2. Performance tests were performed, and the performance tests of all embodiments are summarized in Table 2.

[0086] Table 2 Summary of performance test results of embodiments of the present invention

[0087]

[0088] By comparing the results of the examples, it can be learned that the self-healing low-temperature curing conductive silver paste prepared according to the technical solution of the present invention has a low curing temperature, which reduces the difficulty of the preparation process; after sintering, the silver paste has excellent adhesion, low square resistance and bending resistance, and its performance is better than the conductive silver paste on the market, meeting the technical assessment index values ​​of silver paste for flexible sensors at this stage. Compared with the comparative example, the example introduces surface conductive liquid metal nanoparticles, adopts multi-dimensional micro-nano mixed conductive silver powder, and the highly lamellar silver powder is in direct contact with nano-spherical particles and nanowires to form a smooth three-dimensional conductive network, which effectively reduces the resistivity of the slurry, and shows a small resistance change rate after bending, and has excellent bending resistance; the conductive function ratio is adjusted, and as the proportion of nanowires increases, the bending resistance of the slurry is further enhanced. The embodiment adopts a compounded resin bonding phase, which not only improves the adsorption and binding force between the silver powder and the polar groups of the resin, but also improves the comprehensive performance of the slurry by compounding the softness and hardness of different segment resins, and the adhesion, flexibility, hardness and conductivity are greatly improved; among them, the short straight chain segments of acrylic resin and chlorovinyl resin have strong shrinkage ability, which helps to improve the conductivity of the slurry, and the addition of polyurethane elastomer greatly improves the bending resistance of the slurry; the single polyester resin shows high adhesion and hardness by virtue of the adsorption and binding force of the hydroxyl terminal, but the conductivity and bending resistance are relatively low. In addition, the addition of a closed curing agent enables all embodiments to have a low curing temperature and fast curing ability, thereby improving the process efficiency. In summary, the silver paste prepared by the present invention has high stability, good printing adaptability on flexible substrates, and after rapid curing at 130°C, the slurry has excellent adhesion, low square resistance, high hardness and high bending resistance.

[0089] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0090] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

[0091] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A conductive silver paste, characterized in that: The conductive silver paste comprises the following components: multi-dimensional micro-nano conductive silver powder, surface conductive liquid metal nanoparticles, multi-system organic resin bonding phase, closed curing agent, mixed organic solvent and various additives; wherein the mass parts of each component are: The mass proportion of the multi-dimensional micro-nano conductive silver powder is 60-90 parts; The mass parts of the surface conductive liquid metal nanoparticles are 5-10 parts; The mass proportion of the multi-system organic resin bonding phase is 0.1-10 parts; The mass fraction of the blocked curing agent is 0.1-5 parts; The mass parts of the mixed organic solvent are 5-20 parts; The mass parts of each type of additive are 0.1-10 parts.

2. The conductive silver paste according to claim 1, characterized in that: The multi-dimensional micro-nano conductive silver powder includes silver powders of various dimensions, shapes and particle sizes; The plurality of silver powders of different dimensions, different shapes and different particle sizes include a plurality of silver nanowires, flaky silver powders and spherical silver powders; The length of the silver nanowire is 20-60 μm, and the diameter of the silver nanowire is 10-30 nm; The particle size of the flaky silver powder is 2.0-7.0 μm; the particle size of the spherical silver powder is 5-300 nm; In the multi-dimensional micro-nano conductive silver powder, the silver nanowires account for 2%-15%, and the spherical silver powder accounts for 2%-30%.

3. The conductive silver paste according to claim 1, characterized in that: The surface conductive liquid metal nanoparticles include metal gallium and a gallium alloy associated with the metal gallium; The gallium alloy comprises at least one of a gallium-tin alloy, a gallium-indium alloy, a gallium-indium-tin alloy and a gallium-indium-tin-zinc alloy; The surface conductive liquid metal nanoparticles are prepared by: (1) using gallium-based liquid metal composed of metal gallium and a gallium alloy associated with the metal gallium as an initial raw material, and adding a precursor solution to the initial raw material; (2) placing the initial raw material after adding the precursor solution into a microfluidic ultrasonic reaction device for reaction to obtain the surface conductive liquid metal nanoparticles; The precursor solution includes multiple types of toluene, polyethylene vinyl acetate and diamino peroxide.

4. The conductive silver paste according to claim 1, characterized in that: The multi-system organic resin bonding phase is a mixture of polyester resin, acrylic resin and polyurethane; The polyester resin is a polyester resin with a linear structure and a hydroxyl terminal, and the proportion of the polyester resin in the multi-system organic resin binder phase is 35%-65%.

5. The conductive silver paste according to claim 1, characterized in that: The blocked curing agent includes aliphatic diisocyanate, and the deblocking temperature of the blocked curing agent is 100-150°C.

6. The conductive silver paste according to claim 1, characterized in that: The mixed organic solvent includes two or more of butyl carbitol, terpineol, N-methyl pyrrolidone, alkylbenzene, butyl carbitol acetate and mixed dibasic ester.

7. The conductive silver paste according to claim 1, characterized in that: The various additives include modified urea, polysiloxane, organic bentonite and polyamide wax; among the various additives, the modified urea accounts for 0.2%-1%, the polysiloxane accounts for 0.1%-4%, the organic bentonite accounts for 0.1%-1%, and the polyamide wax accounts for 0.1%-3%.

8. A method for preparing a conductive silver paste according to any one of claims 1 to 7, characterized in that: include: (1) Weighing ferric chloride, silver nitrate, ethylene glycol and polyvinyl pyrrolidone surfactant by weight, adding ferric chloride, silver nitrate, ethylene glycol and polyvinyl pyrrolidone surfactant into a three-necked round-bottom flask, and heating at 140° C. for 4 h to prepare a dispersion of silver nanowires; (2) weighing toluene, polyethylene vinyl acetate, diamino peroxide and liquid metal by weight, adding the toluene, polyethylene vinyl acetate, diamino peroxide and liquid metal into an ultrasonic reaction microfluidic channel, ultrasonicating at 30° C. for 20 min to prepare a dispersion of the surface conductive liquid metal nanoparticles, and centrifuging the dispersion of the surface conductive liquid metal nanoparticles to obtain ultrafine surface conductive liquid metal nanoparticles; (3) taking a plurality of organic resin binder phases and a plurality of organic solvents by weight, and adding the organic resin binder phases and the organic solvents to the prepared silver nanowire dispersion to obtain an organic mixed solution containing silver nanowires; (4) placing the organic mixed solution containing the silver nanowires into a high-speed dispersion kettle, and stirring the organic mixed solution containing the silver nanowires at a constant temperature until it is homogeneous, thereby obtaining an organic carrier containing the silver nanowires; (5) adding flaky silver powder and spherical silver powder to an organic carrier containing silver nanowires to obtain an organic mixed solution containing silver nanowires and nano-silver powder, and placing the organic mixed solution containing silver nanowires and nano-silver powder into a planetary mixer and continuing to stir to prepare a uniform slurry; (6) adding an organic additive and a blocked curing agent to the slurry in the uniform state, continuing stirring to adjust the viscosity and thixotropic properties of the slurry in the uniform state, and placing the slurry after the viscosity and performance are adjusted into a three-roll grinder to adjust the slurry fineness to obtain the final self-repairing low-temperature curing conductive silver paste.

9. The method for preparing a conductive silver paste according to claim 8, characterized in that: In the process of preparing the dispersion of silver nanowires, the preparation method used is the polyol method; In the process of preparing a dispersion of silver nanowires based on the polyol method, after the isothermal reaction in a three-necked round-bottom flask, the three-necked round-bottom flask needs to be quickly placed in ice cubes for cooling, and acetone is added to the cooled three-necked round-bottom flask and centrifuged several times to obtain the dispersion of the silver nanowires.

10. The method for preparing a conductive silver paste according to claim 8, characterized in that: The rotation speed of the high-speed dispersing kettle is 1000-5000 rpm, the dispersing temperature of the high-speed dispersing kettle is controlled at 65-95° C., and the stirring and mixing time is 10-30 minutes; The revolution speed of the planetary mixer is 1000-2200 rpm, and the rotation speed of the planetary mixer is 700-1400 rpm; The spacing of the three-roll mill is adjusted to 2-25 μm, and the rotation speed is controlled at 300-500 rpm; In the process of curing the uniform slurry, the curing temperature used is 100-150° C., and the curing time used is 10-30 minutes.

Citation Information

Cited By

  • Conductive silver paste and preparation method thereof

    CN119626627A

  • Silver paste, preparation method thereof and photovoltaic cell

    CN119626628A

  • Silver paste for photovoltaic cell and preparation method of silver paste for photovoltaic cell

    CN121790055A